Decisive Techniques for Ippon in Elite Women’s Judo: A Tactical Analysis from the Rio 2016 and Tokyo 2020 Olympic Games - Alex Ojeda-Aravena; David Moronta; Bibi Calvo-Rico; Jairo Azócar-Gallardo; José Manuel García-García (Applied Sciences)
Olympic women’s judo has increased in complexity and competitiveness, demanding detailed tactical analysis. This observational study aimed to examine the relationship between the results of combats (Wazari [half point] vs. Ippon [full point]) and the techniques used in women’s judo combats in the Rio 2016 and Tokyo 2020 Olympic Games. A significant association was found between technique type and contest outcome (χ2 = 40.004, df = 6, p < 0.001): Nage Waza (throwing techniques) produced 92.3% of Wazari, whereas Katame Waza (groundwork techniques) accounted for 61.1% of Ippon. Subgroup analysis confirmed these relationships (χ2 = 17.217, df = 6, p = 0.009; Cramer’s V = 0.745), with Ashiwaza (foot/leg techniques) dominating Wazari. Uchimata was the most frequently used technique in the repechage (20%), bronze medal (22.6%), and final (23.1%) matches. In lightweights, Katame Waza dominated Ippon in finals (53.8%, χ2 = 4.000, p = 0.046), while Nage Waza secured all Wazari. Middleweights also showed strong associations (χ2 = 14.745, df = 1, p < 0.001; 93.9% of Wazari by Nage Waza). Although no significant association was found for heavyweights (χ2 = 7.535, df = 1, p = 0.095), Katame Waza prevailed in Ippon (69.2%). These findings provide a tactical framework for tailoring technique-specific training by weight category and tournament phase to optimize outcomes in elite female judo.